Pelaksanaan Rekonstruksi Terhadap Tindak Pidana Yang Dilakukan Oleh Anak Menurut Undang-Undang Nomor 35 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak - Panji Bimantara Simbiring; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
By universal child has the human rights protected by law, applicable even in the womb, because the children are also entitled to legal protection for all the activities that lead to growth and development in the future. Law Number. 23 of 2002 on Child Protection. Affirming that the state, the government, communities, families and the elderly memunyai responsibility for the maintenance and protection of children. As for the purpose of writing this essay, namely: First, How urgency against children in conflict with the law in carrying out the reconstruction process under Act No. 35 of 2014 on the Amendment of Act No. 23 of 2002 regarding Child Protection. Second, the idea of reconstruction How do children in conflict with the law under Act No. 35 of 2014 on the Amendment of Act No. 23 of 2002 regarding Child Protection.This research is a law with doctrinal normative approach that is research done by researching library materials or secondary data. Judging of its kind, this study were classified into normative legal research (Library Research), which is the study which is based on the books or literature in the library.The conclusion of this study is, first, Children in conflict with the law in the reconstruction process in the criminal justice system should be specifically noted. Indonesian National Police Resort Bengkalis Sector High Cliff, the investigator must always look at the interest of the child, and the arrangement of the reconstruction is still fragmented in the Book of the Law of Criminal Law (Criminal Code) provides no legal protection of children as Act Number. 35 of 2014 on the change of Act Number. 23 of 2003 on Protection of Children. Second, the idea of the protection of children who perform reconstruction to ensure and protect children and their rights and non-discrimination. Legal instruments on the protection of children on the specificity of the reconstruction as it should be. Implementation recontruksi carried children in conflict with the law have not managed to ensure the protection and enforcement of children's rights. This will require support arrangements are clearly positive law so that law enforcement agencies in their implementation have a clear juridical grip in handling troubled child process with the law when meelakukan reproduce or rekonstruksi.Saran author of the issues examined are the First, In dealing with a case against children in conflict with the law in a clear form of criminal act committed by the child needs to do reconstruction. Should base their legitimacy on the setting of reconstruction on children in conflict with the law by investigators. Second, the legal context of child protection, when children in conflict with the law through a policy against must be done carefully so as not to cause stigma for the child, therefore, from the perspective of reconstruction does not put pressure on children in conflict with the law. can be implemented properly and fair in order to satisfy the justice in accordance with the principle of child protection. Need for Indonesian Child Protection Commission (KPAI) which is included in order to provide assistance in full in the Indonesian justice system and restorative justice approaches.Keywords: Protection - Legal - Children